HUBUNGAN USIA DENGAN PERDARAHAN POSTPARTUM ( ATONIA UTERI ) DI KLINIK RAMLAH PARJIB SAMARINDA TAHUN 2016 - Rahmawati rahma rahmawati (MMJ (Mahakam Midwifery Journal), 2017)
Abstract Background: In Indonesia, maternal mortality is 228/100,000 live births reported in the frequency range between 9.8%-25.5%. Postpartum hemorrhage is one of the main causes of maternal deaths. The number of postpartum bleeding (uterine atony). Rise at the age of 20 years and <. 35 years old. The purpose of this research aims to find out and analyse the existence of relationship of postpartum hemorrhage with age. This research is the research of analytic approach of Cross Sectional. Method of sampling in the sample Purposiv. The number of samples of maternal postpartum hemorrhage with 30 proportion of postpartum haemorrhage due to uterine atony as many as 20 cases (66.7%) Obtained from the medical record at the clinic Ramlah parjib Samarinda Year 2016. Research results on the test with the test statisti Chi Square (the square) with the SPSS program. The results of the statistical test chi square results obtained at level α = 0.05 significant with a P value of 0.030. Mean P value α <. so, in conclusion the P value is thus α < Ha was accepted, meaning that there is a significant relationship between age with postpartum Bleeding (uterine atony). Summary conclusion So there is a relationship of age with postpartum bleeding (uterine atony). Advice for health institutions and agencies to increase socialization, a planned information, directional and continuous about the importance of early detection of dangers of childbirth diusia information on pregnant women to lower the risk of bleeding events postpartum. Keywords : Age, postpartum bleeding (uterine atony) Abstrak Di Indonesia, angka kematian ibu adalah 228/100.000 kelahiran hidup frekuensi di laporkan berkisar antara 9,8%-25,5%. Perdarahan postpartum merupakan salah satu penyebab utama kematian ibu. Jumlah perdarahan postpartum (atonia uteri). Meningkat pada usia <20 tahun dan . 35 tahun. Penelitian ini bertujuan untuk mengetahui dan menganalisa adanya hubungan usia dengan perdarahan postpartum. Penelitian ini merupakan penelitian analitik dengan pendekatan Cross Sectional. Metode pengambilan sampel secara Purposiv Sampel. Jumlah sampel 30 ibu perdarahan postpartum dengan proporsi perdarahan postpartum karena atonia uteri sebanyak 20 kasus (66,7 %) Yang diperoleh dari rekam medis di Klinik Ramlah parjib Samarinda Tahun 2016. Hasil penelitian di uji dengan uji statisti Chi Square (Kuadrat) dengan program SPSS. Hasil Dari hasil uji statistik chi square didapatkan pada taraf signifikan α = 0.05 dengan P value sebesar 0.030. Berarti P value < α. Jadi, kesimpulannya P value < α dengan demikian Ha diterima, yang artinya ada hubungan signifikan antara usia dengan Perdarahan postpartum (atonia uteri). Jadi kesimpulan ada hubungan usia dengan perdarahan postpartum (atonia uteri). Saran Bagi instansi dan institusi kesehatan untuk meningkatkan sosialisasi, informasi yang terencana, terarah dan berkesinambungan tentang pentingnya deteksi dini bahaya persalinan diusia lanjut pada ibu hamil untuk menurunkan resiko kejadian perdarahan post partum. Kata Kunci : “ Usia, Perdarahan Postpartum (Atonia Uteri)”